The Effect of Shot Peening Configurations on Residual Stress of Aluminium 5052 - Anam, Khairul; Purnowidodo, Anindito (International Journal of Integrated Engineering, 2019)
The aim of this study is, by using ï¬nite element analysis (FEA), to investigate the residual stresses and the distributions on the surface of material after shot peening process. The material of aluminium alloy A5052 is assumed as bilinear isotropic hardening. The residual stresses for various combinations of velocity, shot angle, and ball diameter was calculated. In addition, for ball diameter variations, the residual stresses was calculated by using two and three dimensional modeling. Simulation results indicate the residual stresses especially compressive residual stress is increased with increasing the velocity, shot angle, and ball diameter. However, the residual stresses between two and three dimensional modeling is almost similar.